Internalisasi Perilaku Prososial Mahasiwa Melalui Pendidikan Religius - Rinto Al Wafa; Ach. Nurholis Majid (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
Social creatures, humans cannot be separated from relationships with other humans, for this reason humans need interaction with other people in which there are reciprocal relationships between individuals. Likewise with the Ma'had students of the Dirosat Islamiyah Al-Amien Prenduan Institute itself. So, through Islamic boarding school religious education, the internalization of prosocial behavior is the basis for forming students' personalities to create a generation that behaves Islamically. This research aims to find out and describe the process of internalizing student prosocial behavior through religious education at the Ma'had Institute Dirosat Islamiyah Al-Amien Prenduan. This type of research is qualitative research. To obtain appropriate data and information from research, the researcher uses observation, interviews and documentation methods, where the data analysis technique used by the researcher is qualitative descriptive analysis techniques. Based on the research results, it shows that the process of internalizing the prosocial behavior of Ma'had IDIA Prenduan students is carried out by: providing understanding, instilling tolerance in the form of kinship and example. Barriers to the internalization of students' prosocial behavior that often occur are based on factors, namely: a person's personal characteristics, social situation, peers, and personality's inherent cultural background.